Basic income advocates, sober up - Marx, Ive (IZA - Institute of Labor Economics, 2024)
Basic income advocates see a universal income grant, no questions asked, as bringing many potential benefits, not in the least as an ironclad protection against poverty, if set high enough. It is hard to know with any certainty what a world with a sizeable basic income would look like but we can make theoretically and empirically informed guesses about its likely first-round impacts. Neither the insights we get from (quasi-)experimental research nor those from (micro-)simulation modelling are very encouraging. The estimated first-round effects on poverty are for the most part disappointing, especially in countries with comparatively well-functioning social protection systems. Aggregate employment is likely to fall, especially affecting women. It requires an enormous leap of faith to assume that the effects further down the road would be miraculously better. Moreover, there seems to be a vast gap between what people think a basic income would bring them and how it would actually impact them. Under any plausible scenario there would be many net losers. In short, there are few sound reasons at this time to argue for replacing the better performing social protection systems currently in place with a basic income, especially if a more adequate social floor is the main concern.
10419/295780
Keywords: Graue Literatur; basic income; poverty; income distribution; policy interaction